Exclusion of Men from Randomized Phase III Breast Cancer Clinical Trials. (28th April 2020) - Corrigan, Kelsey L.; Mainwaring, Walker; Miller, Austin B.; Lin, Timothy A.; Jethanandani, Amit; Espinoza, Andres F.; Piotrowski, Matt; Fuller, C. David; Stauder, Michael C.; Shaitelman, Simona F.; Perkins, George H.; Woodward, Wendy A.; et al.
Abstract: Male breast cancer treatment regimens are often extrapolated from female‐based studies because of a paucity of literature analyzing male breast cancer. Using ClinicalTrials.gov, we analyzed breast cancer randomized clinical trials (RCTs) to determine which factors were associated with male‐gender inclusion. Of 131 breast cancer RCTs identified, male patients represented 0.087% of the total study population, which is significantly less than the proportion of male patients with breast cancer in the U.S. (0.95%; p < .001). Twenty‐seven trials included male patients (20.6%). Lower rates of male inclusion were seen in trials that randomized or mandated hormone therapy as part of the trial protocol compared with trials that did not randomize or mandate endocrine therapy (2.5% vs. 28.6% male inclusion; p < .001). It is imperative for breast cancer clinical trials to include men when allowable in order to improve generalizability and treatment decisions in male patients with breast cancer. Abstract : To improve generalizability and treatment decisions for male patients, breast cancer clinical trials should include men when possible. This article reports factors associated with male participation in breast cancer studies.